Late subclinical hemolysis and long-term outcomes after aortic valve replacement with On-X mechanical prostheses – a preliminary single-center report - Perek, Bartłomiej; Sławek, Sylwia; Malińska, Agnieszka; Katyńska, Izabela; Puślecki, Mateusz; Szymak-Pawełczyk, Bogumiła; Nowicki, Michał; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Aortic valve replacement (AVR) with a mechanical prosthesis is not free from late complications. Aim : To evaluate the prevalence of subclinical hemolysis after AVR with On-X prostheses and assess its impact on long-term outcomes. Material and methods : The prospective study included 84 consecutive patients aged 58.3 ±10.3 years who underwent AVR. They were retrospectively split into group H (n = 12; 14.3%) with prosthesis-related subclinical hemolysis and a control group (C; n = 72; 85.7%). All operations were performed via median sternotomy using cardio-pulmonary bypass. At the end of follow-up, echocardiography was carried out and blood samples for morphology and biochemistry (lactate dehydrogenase (LDH), bilirubin, haptoglobin) were taken. Results : The rate of subclinical hemolysis in patients with properly working prostheses was 14.3% and it was the highest (33.3%) for the smallest valves. Although an improvement in functional status was noted in both groups, it was less evident in group H than in group C (p = 0.007). At the end of follow-up, 97.2% in group C and 75.0% in group H were found in NYHA classes I and II. Patients in group H had significantly lower hemoglobin, hematocrit, and haptoglobin and higher LDH activity than group C subjects. In group H, systolic gradients of On-X valves were higher whereas effective orifice area was smaller than in group C. Conclusions : Our study proved that prosthesis-induced subclinical hemolysis is seen even after implantation of the latest generation mechanical prostheses, particularly of small diameter, and its degree may impact late outcome.